Impact of Microinsurance Affordability on Profitability of Micro, Small, and Medium Enterprises (MSMEs) in Lagos State, Nigeria - Agboola Omoniyi Oladipupo; Oyede Saheed Adesunkanmi (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
Nigeria has one of the lowest insurance penetration rates in the world possibly owing to the cost of insurance products. The study investigated the impact of microinsurance affordability on MSME's profitability in Nigeria. The study is quantitative employing both survey and cross-sectional research design. A total of four hundred (400) copies of the questionnaire were administered, but only three hundred forty-five (345) copies of the questionnaire were duly filled and used for this study representing an 86.3% response rate. According to the findings, microinsurance affordability has a favorable and considerable impact on MSME's profitability in Nigeria. The study recommended that insurance companies should improve on claims processing, be sincere, and promptly attend to customer's claims because some insurance companies do not always give full details about policies to lure people into buying them.